The accessory subunit B of DNA polymerase γ is required for mitochondrial replisome function - Farge, Géraldine (Oxford University Press, 2007)
The mitochondrial replication machinery in human cells includes the DNA polymerase γ holoenzyme and the TWINKLE helicase. Together, these two factors form a processive replication machinery, a replisome, which can use duplex DNA as template to synthesize long stretches of single-stranded DNA. We here address the importance of the smaller, accessory B subunit of DNA polymerase γ and demonstrate that this subunit is absolutely required for replisome function. The duplex DNA binding activity of the B subunit is needed for coordination of POLγ holoenzyme and TWINKLE helicase activities at the mtDNA replication fork. In the absence of proof for direct physical interactions between the components of the mitochondrial replisome, these functional interactions may explain the strict interdependence of TWINKLE and DNA polymerase γ for mitochondrial DNA synthesis. Furthermore, mutations in TWINKLE as well as in the catalytic A and accessory B subunits of the POLγ holoenzyme, may cause autosomal dominant progressive external ophthalmoplegia, a disorder associated with deletions in mitochondrial DNA. The crucial importance of the B subunit for replisome function may help to explain why mutations in these three proteins cause an identical syndrome.